Assessment of Construction Site Management Practices: A Case Study of a Construction Project in Hargeisa - Abdirisak Mohamed Abdillahi; Savaş Bayram; Zübeyde Özlem Parlak Biçer (Journal of Advanced Research in Natural and Applied Sciences)
The effective management of construction sites is crucial for minimizing risks such as lost productivity, injuries, and theft and ensuring the successful completion of projects. Site management encompasses applying scientific methods and evaluation criteria to plan and organize various production factors, including workforce, machinery, and materials. Managing these factors is vital for transforming raw materials into the final product. Inefficiencies in site management often lead to increased rework, defects, delays, disputes, and cost overruns, affecting construction projects. This study evaluated a construction project in Hargeisa, utilizing six established construction site management practices as assessment criteria. The findings reveal significant shortcomings in the site management practices, with 15 key items within these practices either partially performed or not performed. These inadequacies mirror the broader challenges construction sites face in Hargeisa, highlighting the need for a more robust and comprehensive site management approach. The study’s findings indicate that implementing an improved site management procedure is critical for the long-term sustainability of the construction industry in Hargeisa. Such improvements are essential for enhancing project efficiency, reducing costs, and safeguarding the health and safety of workers and all individuals involved in the construction projects. Based on the evaluation, the study proposes specific recommendations to address these shortcomings, aiming to contribute to advancing construction site management practices in the region. These recommendations could significantly improve project outcomes, worker safety, and industry standards.